2019
DOI: 10.1002/we.2332
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation impact of in situ and remote sensing meteorological observations on wind power forecasts during the first Wind Forecast Improvement Project (WFIP)

Abstract: During the first Wind Forecast Improvement Project (WFIP), new meteorological observations were collected from a large suite of instruments, including wind velocities measured on networks of tall towers provided by wind industry partners, wind speeds measured by cup anemometers mounted on the nacelles of wind turbines, and wind profiles by networks of Doppler sodars and radar wind profilers. Previous data denial studies found a significant improvement of up to 6% root mean squared error (RMSE) reduction for sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The improvements are analyzed in terms of the new physics (EXP vs. CNT runs) as well as horizontal grid spacing of the models (HRRRNEST vs. HRRR runs), first separately and then combining the impact of the two (HRRRNEST EXP vs. HRRR CNT). Finally, we evaluate the dependence of the improvements on the dominant meteorological phenomena of the area (Shaw et al, 2019), including cold pools (Whiteman et al, 2001;Zhong et al, 2001;McCaffrey et al, 2019), gap flows Mass, 2002, 2004), easterly flows (Neiman et al, 2018), mountain L. Bianco et al: Model improvements on 80 m wind speeds waves (Durran, 1990(Durran, , 2003, topographic wakes, and convective outflows (Mueller and Carbone, 1987).…”
Section: Statistical Results As a Function Of The Site Elevationmentioning
confidence: 99%
“…The improvements are analyzed in terms of the new physics (EXP vs. CNT runs) as well as horizontal grid spacing of the models (HRRRNEST vs. HRRR runs), first separately and then combining the impact of the two (HRRRNEST EXP vs. HRRR CNT). Finally, we evaluate the dependence of the improvements on the dominant meteorological phenomena of the area (Shaw et al, 2019), including cold pools (Whiteman et al, 2001;Zhong et al, 2001;McCaffrey et al, 2019), gap flows Mass, 2002, 2004), easterly flows (Neiman et al, 2018), mountain L. Bianco et al: Model improvements on 80 m wind speeds waves (Durran, 1990(Durran, , 2003, topographic wakes, and convective outflows (Mueller and Carbone, 1987).…”
Section: Statistical Results As a Function Of The Site Elevationmentioning
confidence: 99%
“…The percent improvement of the skill of RAP simulations at forecasting ramp events is shown when assimilating the combined WFIP remote sensors and in situ instruments (black bars), when assimilating the WFIP remote sensor observations (green bars), and when assimilating the WFIP in situ observations (magenta bars). Similar to what was found by Wilczak et al, the impact due to the assimilation of additional in situ observations has a significant initial impact that diminishes rapidly over several hours. In comparison, assimilation of the less numerous remote sensing observations has a smaller initial impact but remains positive for a longer forecast lead times.…”
Section: Resultsmentioning
confidence: 99%
“…A previous analysis of these model simulations found that the relative percent improvement in model forecast skill of the Experimental Run's RMSE and coefficient of determination of turbine hub‐height winds (at forecast hour 1) was 6%, for both the NSA and SSA, decreasing at longer forecast horizons . A later, second analysis investigated the impact of different components of the WFIP observing system, by separating the instrumentation into two groups, remote sensors (WPRs and sodars) and in situ (tall tower vector winds and nacelle anemometer wind speeds), and assimilating them each independently for a subset of two of the six data denial periods (13‐20 October 2011 and 7‐15 January 2012) . That analysis demonstrated that the large numbers of in situ observations had a significant initial impact that diminished rapidly after only several hours, while the less numerous remote sensing instruments had a smaller initial impact that improved the forecasts for a longer time, due to their observing a deeper layer of the atmosphere.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…The biggest improvements were from the boundary-layer, finite differencing, and the SGS drag, which improved the representation of turbulent mixing in stable boundary layers. The reader is referred to Olson et al (2019a;2019b) for more details on the differences between the CTL and EXP model configurations. For our analysis, in order to compare to the observations, the 80m wind field model output is horizontally bi-linearly interpolated to the 22 site locations using the 4 closest grid points.…”
Section: Nwp Modelsmentioning
confidence: 99%